Analysis of Factors Affecting Accountability of Village Fund Management - Tri Ratna Sari; Abdul Rohman (Quantitative Economics and Management Studies, 2024)
The responsibility of the village government is to enforce accountability to the community. If there are irregularities in the management of village funds, the community's trust in the village government could decrease. The aim of this research is to examine the impact of various factors that influence the accountability of village fund management. The population in this study was from all villages in the districts of Skanto , Arso , Arso Barat, and Mannem. The sampling process uses purposive sampling, namely selecting village officials involved in managing village funds. This group consists of the village head, secretary and treasurer. Primary data collection was carried out through distributing questionnaires which were given directly to respondents. Multiple linear regression is a statistical tool used for data analysis. Next, the data is processed using SPSS 26.0 software. Based on research, the effectiveness of village officials and internal control systems is known to have a positive impact on the accountability of village fund management. In contrast, leadership and integrity systems do not appear to have a significant influence.